From a threatened life to a longed-for life: Glimpses of a theology of life in dialogue with literature (PONTIFICIA UNIV CATOLICA CHILE, FACULTAD TEOLOGIA, 2007)
Life, that mystery at once fascinating and vulnerable, was examined at a recent faculty seminar. Within this framework, the author of this article endeavors to listen to the voice of the writers of two novels: Pedro Paramo (1955) by the Mexican writer Juan Rulfo (1917-1986), and La amortajada ["The Shrouded Woman"] (1938) by the Chilean writer Maria Luisa Bombal (1910-1980). In both cases the literary characters speak to us from the other side of the grave, in order to radicalize questions about life, about the meetings that have marked the characters, about the body as mediation of those meetings. Thus, a dialogue emerges from these figures beyond life, in which the great eschatological themes of Pauline theology resonate forcefully and, at the same time, permit a deep reflection upon eternal life as always being with the Lord, as well as regarding the kind of body with which we will rise again.